2020
DOI: 10.32604/cmc.2020.013120
|View full text |Cite
|
Sign up to set email alerts
|

Dual Branches of MHD Three-Dimensional Rotating Flow of Hybrid Nanofluid on Nonlinear Shrinking Sheet

Abstract: In this study, magnetohydrodynamic (MHD) three-dimensional (3D) flow of alumina (Al 2 O 3 ) and copper (Cu) nanoparticles of an electrically conducting incompressible fluid in a rotating frame has been investigated. The shrinking surface generates the flow that also has been examined. The single-phase (i.e., Tiwari and Das) model is implemented for the hybrid nanofluid transport phenomena. Results for alumina and copper nanomaterials in the water base fluid are achieved. Boundary layer approximations are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This set of BVP problems is then solved by implementing Bvp4c code in MATLAB, along with the identified boundary conditions. The "inbuilt MATLAB code bvp4c" implements the three-stage Lobatto IIIa method [47], [38], [27].…”
Section: Numerical Solutionmentioning
confidence: 99%
“…This set of BVP problems is then solved by implementing Bvp4c code in MATLAB, along with the identified boundary conditions. The "inbuilt MATLAB code bvp4c" implements the three-stage Lobatto IIIa method [47], [38], [27].…”
Section: Numerical Solutionmentioning
confidence: 99%
“…They revealed that the addition of nanoparticles volumetric concentration diminished the blood velocity and temperature profiles. The discussions regarding the thermal and flow characteristics of hybrid nanofluids were reported by Khashi'ie et al [21][22][23][24] for disc case, Khan et al [25][26][27] for wedge and cylinder geometries and Lund et al [28][29][30][31] for stretching/shrinking plate. The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al [32][33][34][35][36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
“…[25–27] for wedge and cylinder geometries and Lund et al. [28–31] for stretching/shrinking plate. The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al.…”
Section: Introductionmentioning
confidence: 99%
“…They inferred that the magnetic field grows both the momentum and temperature of the liquid. Lund et al, [13] inspected MHD 3D Cu-Al2O3/H2O on a nonlinear shrinking plate using the 3-level Lobato Illa method and concluded that the magnetic effect diminishes both the velocity and temperature of the fluid. Another study by Lund et al, [14] also proved that the magnetic field slows down the speed of the fluid.…”
Section: Introductionmentioning
confidence: 99%